Adsorption Process Optimization and Adsorbent Evaluation Based on Langmuir Isotherm Model - Wang, Jinyu (Langmuir : the ACS journal of surfaces and colloids, 2023)
Adsorption separation is considered one of the most commonly used gas purification methods. At present, the most widely used adsorption methods are mainly pressure swing adsorption (PSA) and temperature swing adsorption (TSA). In both adsorption methods, a comprehensive understanding of the equilibrium data and the adsorption capacity of the adsorbent is essential for process design and optimization, and the adsorption isotherm can provide a powerful aid in this regard. In this study, through mathematical analysis of the Langmuir isotherm model, the optimal cyclic adsorption conditions and the optimal thermodynamic parameters (entropy change and enthalpy change) under PSA and TSA were obtained. In addition, the isotherm model can be used to predict the isobaric adsorption capacity, and the objective function was established according to the cyclic adsorption capacity and the regeneration sensible heat consumption per unit adsorption capacity to calculate the optimal adsorption/desorption temperatures and optimal cyclic adsorption capacity of various adsorbents